Using the negative hyperconjugation effect of pentafluorosulfanyl acceptors to enhance two-photon absorption in push–pull chromophores - Gautam, Prabhat (2020)
A series of first-generation pentafluorosulfanyl-substituted chromophores with high two-photon cross-sections is described. The pentafluorosulfanyl functional group is a very intriguing moiety that possesses not only a strong inductive effect due to its high electronegativity but also a sizable resonance acceptor constant due to negative hyperconjugation involving the sulfur(VI) center. This negative hyperconjugation effect imparts cationic character to the sulfurs, a feature that we exploit in the design of potent two-photon-absorbing systems where the pentafluorosulfanyl groups serve as strong terminal acceptors. Herein, we report five multibranched triarylamine-based dyes with two-photon absorption cross-sections ranging from 1100–2200 GM. This demonstrates for the first time that when coupled to a suitable donor, pentafluorosulfanyl acceptors are a viable molecular handle for designing large cross-sections in relatively small metal-free π-conjugated systems.